Genomic comparison of methicillin-resistant Staphylococcus aureus CC398 isolates from livestock, meat and humans in the Netherlands - van Duijkeren, Engeline; Dierikx, Cindy M.; Brouwer, Michael S. M.; Veldman, Kees T.; Wullings, Bart; Rapallini, Michel; Wit, Ben; Cuperus, Tryntsje; Hengeveld, Paul D.; van Hoek, Angela H. A. M.; de Haan, Angela; Witteveen, Sandra; et al. (Frontiers in Microbiology, 2026)
Since 2003, methicillin-resistant Staphylococcus aureus clonal complex 398 (MRSA- CC398) emerged in livestock. To assess possible transfer of resistant strains, animal-related MRSA- CC398 were characterized and compared to those from humans. For that purpose, MRSA-CC398 isolates (n = 2,569) from the national human MRSA surveillance (n = 1,758) and animal-related isolates (n = 811) were included for analysis. Next-generation sequencing data were used for MLST, whole-genome MLST (wgMLST) and identification of resistance/virulence genes. wgMLST showed that animal- and human-related MRSA-CC398 isolates grouped together in four groups termed A (n = 205), B (n = 308), C (n = 382), and D (n = 1,674) varying 103–139 wgMLST alleles between groups. Some animal-related isolates were closely related to human isolates or to animal isolates from other farms in all four groups. There were no groups containing animal isolates only. Differences were identified in the prevalence of virulence- and resistance genes between MRSA-CC398 originating from human- and animal-related isolates and between the four groups. Specifically, one branch within group C comprised only MRSA-CC398 from humans; these isolates were often ST1232, and carried lukS-PV/lukF-PV (PVL)-, sak, scn, ant(9)-Ia, and erm(A)-variant genes. Persons carrying this lineage rarely reported professional livestock contact, lived in areas with low pig density, and had more often a clinical infection compared to persons carrying non-ST1232. The MRSA-CC398 population in the Netherlands is diverse and comprised of four groups with distinct genomic signature. Although most MRSA-CC398 are still livestock-associated, a PVL-positive human-related lineage in CC398 has emerged in the Netherlands among the population in the absence of livestock contact.